Identifikasi Rhodamin B Dan Persepsi Siswa Terhadap Jajanan Di Sekolah Dasar Sekitar Kampus UMS - Taufik, Muhamad; , Rusdin Rauf, STP., MP; , Eni Purwani, S.Si., M.Si (2016)
Background: Food safety issues, especially the use of harmful chemicals in food is still a major problem in Indonesia. Most cases are found in the school environment where consumers mostly school children. Results of research by BPOM in 2013 showed that Rhodamine B is founded most. Objective: identification of rhodamine B and assess student perception of snacks at schools around the campus of the University of Muhammadiyah Surakarta. Methods : Descriptive study with a sample of 62 students in grade IV and V obtained by purposive sampling in 4 elementary school.Data perception and snacks obtained through questionnaire.Data Identification of rhodamine B on snacks obtained through rhodamine B test kit.The data were presented in the form of frequency and percentage. Result: Of 62 students in four elementary schools, 87.5% of students have good perception regarding safety of snacks and 80.2% of students have good perception color of snacks. Of total 22 samples examined 10 samples snacks (45.4%) contain rhodamine B with 8 samples snacks come from the canteen and 2 samples snacks samples come from outside the school. Conclution: Most students have good perception regarding safety and color of snacks. Almost half of samples contain rhodamine B. The school to be more concerned about the snacks are mainly sold in the school canteen and health authorities should educate primary school students about healthy snacks